Sheep-oil palm integration: Growth performance of dorset x malin and dorset x siamese long tail sheep - Chaiyawan, Wattanachant; Ismail, Dahlan; Abdullah, Zulkifli; Rajion, Mohamed Ali (Universiti Putra Malaysia Press, 1997)
This study involved the integration of sheep into oil palm plantations. The growth rates of 25% Dorset x 75% Malin (DMalin) and 25% Dorset x 75% Siamese Long Tail (DSLT) sheep raised in 9, 13, 16 and 21 year old oil palm plantations were evaluated. The measurements were taken by randomly sampling from the flock at birth, 2, 4, 6, 8 and 10 months of age. The relationship between body weight and age was determined by Brody's model. Consequently, the growth models of sheep were 1) BW = 17.9715 (1-0.9113 exp(-0.0049*AGE)) for DMalin male, 2) BW = 17.7792 (1-0.9230 exp(-0.005*AGE)) for D1V1alin female, 3) BW = 21 (1-0.8778 exp(0.0049* AGAj) for DSLT male and 4) BW = 18.7301 (1-0.8613 exp(-0.0059*AGE)) for DSLT female. The average dai(y gain ofDMalin and DSLT sheep from birth to 10 months of age was 41.0 and 54.1 gm/head/ day, respectively. The males were slightly heavier than the females. Daily weight gains of sheep wae related to the limited grazing period and low quantity of herbage available in old oil palm plantations.